WADA, IOC Testing for Erythropoietin is faked - Koudinov, A. R. (Doping Journal, 2006)
The study published in Blood, the major international scientific journal on blood science and medicine [1], suggests that International Olympic Committee (IOC) and World Anti-Doping Agency (WADA) testing for Erythropoietin (Epo) is based on faked science. Straightforward experimental protocol shows that widely-used by IOC and WADA Epo test can lead to the false-positive detection of rhEpo in post-exercise, protein-rich urine of the endurance sports athletes. The reported study leaves little doubt that the major urinary protein that WADA test visualizes with the ani-Epo antibodies is not Epo.